Associations between symptoms of borderline personality disorder and suicidality in inpatient adolescents: The significance of identity disturbance. (June 2022) - Sekowski, Marcin; Gambin, Malgorzata; Sumlin, Eric; Sharp, Carla
Highlights: Of the BPD symptoms, identity disturbance, chronic emptiness, abandonment avoidance and transient paranoia were the most robust correlates of greater suicidal ideation in inpatient adolescents. Only identity disturbance was positively associated with suicide attempts. Overall BPD severity was positively related to suicidal ideation and suicide attempts. All of these associations were significant when controlling for age, gender, and severity of depressive symptoms. Abstract: Several studies report that borderline personality disorder (BPD) is a risk factor for suicidality in adults. However, this issue requires further research in adolescents, as it is not clear which individual BPD symptoms are significant correlates of suicidality in this age group. The main aim of the current study was to test which symptoms of BPD are associated with suicidality in adolescent inpatients, even when controlling for age, gender, and depressive symptoms. Inpatient adolescents ( N = 339) aged 12–17 years completed the Childhood Interview for DSM-IV Borderline Personality Disorder, the Beck Depression Inventory-II, the Modified Scale for Suicidal Ideation, and reported their number of lifetime suicide attempts. Multivariable regression analyses showed that, after controlling for confounding variables, overall BPD symptom severity was positively related to suicidal ideation and suicide attempts. Of the individual BPD symptoms, identity disturbance, chronic emptiness, avoid abandonment, and transient paranoia were the most robust correlates of suicidal ideation intensity, and only identity disturbance was associated with the number of lifetime suicide attempts. To assess the risk of suicidality in youth, it is essential to assess for BPD symptoms; it is important to focus on adolescents' subjective feelings to assess the severity of identity disturbance and chronic emptiness.